The Strategic Role of Family Business In Entrepreneurship Education For Students With Special Needs: An Indonesian Perspective Systematic Literature Review (SLR) - Wahyudi, Dwi; Dwi Santoso; Chozin; Sunariyadi; Andy Prasetyo Wati; Ludi Wishnu Wardana (International Journal of Technology and Education Research, 2025)
This research aims to systematically examine the strategic role of family businesses in entrepreneurship education for students with special needs in Indonesia. Entrepreneurship education has become an important approach to increase economic independence, especially for individuals with special needs who face challenges in accessing formal employment. Family business as a family-based economic unit has great potential as a contextualized, flexible and supportive means of entrepreneurship learning. This Systematic Literature Review (SLR) analyzes 25 relevant national and international journal articles, published between 2019-2025, with a focus on the integration of family business in entrepreneurship education for people with disabilities. The results show that family businesses can provide an inclusive learning environment, build practical skills, and strengthen family involvement in the education process. However, challenges still arise in the form of limited resources, access to training and supporting policies. This study recommends the need for collaboration between schools, families and government in designing a family business-based entrepreneurship curriculum that is adaptive to the needs of students with special needs. The findings make an important contribution to the development of a more inclusive and sustainable entrepreneurship education model in Indonesia.